CHARACTER ESTABLISHMENT OF CHILDREN THROUGH LIVING HISTORY LEARNING - Muh. Haris Zubaidillah; Husin; Rizka Maulida; Abdul Rashid bin Abdul Aziz (The International Conference on Education, Social Sciences and Technology (ICESST), 2022)
The character of a child formed since he was small, whether consciously or not, will influence the way the individual perceives himself and his environment which will be reflected in his daily behavior. What is prioritized in character education is the strengthening of religious values, as a means to form a generation that has character, has noble character and loves the sunnah of the Prophet. One of them is in this study, which aims to shape children's character through living hadith learning in the form of a module which contains several components, namely: definitions, to clarify children's understanding of the title being studied, motivational sentences as children's learning motivation, adab-adab, namely a series of daily sunnah practices that students can carry out and get used to, prayer, namely prayers taken from hadiths related to the material being studied, and memorized hadiths, namely short hadiths that students can memorize. This research was conducted at SDN Muara Baruh, North Amuntai District. This study uses a qualitative descriptive field research method. The results of this study indicate that learning living hadith is very helpful in forming children's attitudes and behavior in everyday life, such as the etiquette of wearing shoes and sandals.